2021
DOI: 10.1007/s11606-020-06357-1
|View full text |Cite
|
Sign up to set email alerts
|

Prior Choices of Between-Study Heterogeneity in Contemporary Bayesian Network Meta-analyses: an Empirical Study

Abstract: BACKGROUND: Network meta-analysis (NMA) is a popular tool to compare multiple treatments in medical research. It is frequently implemented via Bayesian methods. The prior choice of between-study heterogeneity is critical in Bayesian NMAs. This study evaluates the impact of different priors for heterogeneity on NMA results. METHODS:We identified all NMAs with binary outcomes published in The BMJ, JAMA, and The Lancet during 2010-2018, and extracted information about their prior choices for heterogeneity. Our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…From the Bayesian perspective, penalizing the between-study variance is equivalent to assigning a prior distribution to the variance component 𝜏 2 or 𝜏. Meta-analysts may use informative priors based on external evidence to aid the estimation of the between-study variance, which may be particularly helpful for meta-analyses with a relatively small number of studies. 58,59…”
Section: Discussionmentioning
confidence: 99%
“…From the Bayesian perspective, penalizing the between-study variance is equivalent to assigning a prior distribution to the variance component 𝜏 2 or 𝜏. Meta-analysts may use informative priors based on external evidence to aid the estimation of the between-study variance, which may be particularly helpful for meta-analyses with a relatively small number of studies. 58,59…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the vague priors, secondary analyses were performed for each NMA using informative priors [ 32 , 36 ]. Specifically, based on the recommendations from Turner et al [ 32 ], we used the log-normal priors LN (−2.01, 1.64 2 ) and LN (−2.13, 1.58 2 ) for the heterogeneity variances in the smoking cessation and all-grade TrAEs data, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the current literature, many NMAs are performed using Bayesian approaches alongside frequentist ones [ 26 – 28 ]. Bayesian approaches offer additional flexibility compared to frequentist approaches, e.g., by specifying informative priors and sophisticated variance-covariance structures within multi-arm studies [ 29 – 36 ]. This article extends the P-score to a future study setting under the Bayesian framework, with the focus on NMAs with binary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, we want the observed data to have the most influence on the posterior effect estimates and, thus, often non‐informative or minimally informative prior distributions (in which the posterior distribution is determined as completely or as minimally as possible by the observed data) are used 23 31 32. The prior distribution should be within the range of plausible values for the pooled intervention effect and, if the prior is to be non‐informative (or vague or uniform), it should be very large, which means that the distribution is essentially flat over the plausible range of values for the treatment effect 31–33. Despite the importance of prior distributions, a recent review of 44 Bayesian NMAs published in leading general medical journals found that approximately half did not specify their choice of heterogeneity prior distributions and 84% failed to provide a rationale for their selected priors 33…”
Section: Introductionmentioning
confidence: 99%
“…The prior distribution should be within the range of plausible values for the pooled intervention effect and, if the prior is to be non‐informative (or vague or uniform), it should be very large, which means that the distribution is essentially flat over the plausible range of values for the treatment effect 31–33. Despite the importance of prior distributions, a recent review of 44 Bayesian NMAs published in leading general medical journals found that approximately half did not specify their choice of heterogeneity prior distributions and 84% failed to provide a rationale for their selected priors 33…”
Section: Introductionmentioning
confidence: 99%